Lymphocyte Signal Transduction - Tsoukas, Constantine; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
Signal transduction through leukocyte receptors involves a variety of signaling molecules including kinases, phosphatases, adaptor proteins, small GTPases GTP exchange factors, membrane phospholipids as well as others. These signal transducers, regulated by inter- and intra-molecular interactions, as well as by various post-translational modifications, lead to the activation of transcription factors that mediate cellular differentiation and growth, effector cell functions, and apoptotic cell death. Several investigators from various parts of the world convened at the 3rd Lymphocyte Signal Transduction Workshop in Crete, Greece from May 27 to June 1, 2005 to discuss their most recent findings in leukocyte signaling. This volume represents a collection of topics discussed during the conference.
Protein Kinase C-Theta (PKC?): New Perspectives on Its Functions in T Cell Biology -- Travel Informations on the TEC Kinases during Lymphocyte Activation -- Inducible T Cell Tyrosine Kinase (ITK): Structural Requirements and Actin Polymerization -- Differential Requirements of PI3K Subunits for BCR or BCR/CD19-Induced ERK Activation -- Protein Tyrosine Phosphatases in Human Disease -- The T Cell-Specific Adapter Protein Functions as a Regulator of Peripheral but not Central Immunological Tolerance -- Proximal Signals Controlling B-Cell Antigen Receptor (BCR) Mediated NF-?B Activation -- The Adapter 3BP2: How It Plugs into Leukocyte Signaling -- CTLA-4 Regulation of T Cell Function via RAP-1-Mediated Adhesion -- Protein Crosstalk in Lipid Rafts -- Role of Lipid Rafts in Activation-Induced Cell Death : The Fas Pathway in Aging -- T Cell Response in Aging: Influence of Cellular Cholesterol Modulation -- Lymphocyte Signaling and the Translatability of mRNA -- Protein Arginine Methylation: A New Frontier in T Cell Signal Transduction -- Immune Regulation by Ubiquitin Conjugation -- CTIB (C-Terminus Protein of I?B-?: A Novel Factor Required for Acidic Adaptation -- HIV May Deplete Most CD4 Lymphocytes by a Mechanism Involving Signaling through its Receptors on Non-Permissive Resting Lymphocytes -- Integrating Traditional and Postgenomic Approaches to Investigate Lymphocyte Development and Function -- Phosphoproteomic Analysis of Lymphocyte Signaling.
Keywords: Immunology; Microbiology; Infectious diseases; Immunology; Microbiology; Infectious Diseases